The The Effect of High-Intensity Interval Training on Weight Loss Among Adults - Fachruddin, Ismi Irfiyanti; Nur Asmi (Jurnal Gizi dan Kesehatan Keluarga, 2025)
Weight control is a process of avoiding fat deposits in the body. This depends on the relationship between the amount of food consumed and the amount of energy used. The less you eat and the energy you expend, the more fat deposits will decrease. Weight control is very important for health because obesity can cause heart problems. Physical exercise can help you lose weight faster and make your body healthier and fitter. People on a weight loss diet should do more exercise, but an obese person, even if they are able-bodied, should not suddenly start with strenuous exercise. Exercises suitable for a weight loss program are carried out continuously, over a long period, or often referred to as aerobic exercise. This research is a quasi-experimental study, where variable measurements are carried out before and after being given treatment. This research was conducted for 10 weeks. This research was conducted at Dadi Regional Special Hospital, Makassar, South Sulawesi, with a total of 40 research subjects. The sports training provided is High Intensity Interval Training (Aerobics). Sports training is done 3 times a week. This study found a substantial decrease in weight after a 2-month fitness program, as indicated by a p-value of 0.001 (> 0.05).